Addressing the psychology of financial markets - David Tuckett (Kiel Institute for the World Economy (IfW), 2009)
The author suggests the 2008 financial crisis was the culmination of an accelerating process of financial market evolution that is inherently unstable. From his viewpoint markets are not well organized to manage the power financial assets have to generate emotion and their wider effect on human imagination and judgement, anchored in neurobiology. Judgements and so decisions about risk, reward and the evaluation of success can become systematically compromised because the excitement of potential gain is disconnected from the anxiety of potential consequences; producing groupthink and bubbles. When anxiety breaks through a catastrophic loss of confidence is inevitable. In the aftermath the emotional pain of accepting responsibility prevents lessons being learned. The authors theoretical framework is influenced by modern psychoanalysis drawing on an interview study of international fund managers in 2007. He suggests underlying psychological conflicts have influenced the way market institutions have evolved to compete by selling the promise of exceptional performance. To cope with the expectations upon them, agents are impelled to base their actions on stories which overvalue opportunities and underestimate risks; creating agency issues and facilitating the very process of disconnecting anxiety from excitement which creates bubble potential. Policy implications go well beyond improving regulation and transparency.
Keywords: G01; G18; G28; 330; Financial bubbles; financial crises; group functioning; groupthink; market instability; financial regulation; psychoanalysis; psychology; Finanzmarktkrise; Anlageverhalten; Finanzmarkt; Bubbles; Sozialpsychologie; Erwartungstheorie; Regulierung; Welt